Playing with a Doll Family: Key Characteristics of Junior Preschoolers' Play Behaviour - Vera L. Sukhikh; Nikolai N. Veresov; Margarita N. Gavrilova (Peoples' Friendship University of Russia (RUDN University), 2023)
The age of 3-4 years is the initial stage in the development of pretend play, or play involving an imaginary situation. In this process, the leading role belongs to dramatic play with toys, the importance of which for children's development cannot be underestimated. The qualitative analysis of children's play presented in this research forms part of a large study aimed at identifying the features of children's play and the toy preferences throughout the entire preschool age. Ten 3-4-year-old children during five play sessions were asked to play a story with a doll family. Before and after the play sessions, all children were tested to assess the level of development of executive functions, imagination, and the type of attachment was determined for each child using a survey of teachers and mothers. The video recordings of the play sessions were then analyzed. The purpose of the analysis was to identify the characteristics of 3-4-year-old children's play behavior and to explore the relationship of the play features with the indicators of individual development. The experimental setting with a series of play sessions also made it possible to assess the dynamics in play development for each child. To evaluate the play, the following indicators were used: the theme and content of play, spatial substitution, the extent of elaborateness and stability of the play idea, the level of play actions with a toy, and the elaborateness of role-play interactions. The results showed that the level of development of free play involving an imaginary situation for 3-4-year-old children could be defined as generally low, regardless of the level of individual development indicators. A comparison of the first and the fifth play sessions did not reveal any positive dynamics in the level of play development. These results indicate the important role of adult participation in the support and development of children's play. They can form the basis for the practical recommendations for teachers and parents how to scaffold the playing process of 3-4 years old children.